Proline dehydrogenase, a rate-limiting catabolic enzyme, affecting the growth and pathogenicity of Toxoplasma gondii tachyzoites by regulating the proline metabolism and mitochondrial function of the parasite - Xiao-Ling Geng; Jing-Yu Li; Huan-Yu Xu; Jiang-Ping Wu; De-Liang Tao; Jin-Ming Chen; Ying-Ying Fan; Xin Yang; Jun-Ke Song; Guang-Hui Zhao (Parasites & Vectors)
Abstract Background The pathogenicity of Toxoplasma gondii is closely associated with its intracellular lytic cycle in host cells. Currently, the mechanisms by which T. gondii completes the lytic cycle remain unclear. The proline metabolism has been reported to be crucial for intracellular growth of pathogens by providing energy and nutrients. However, it remains unclear whether the intracellular growth and pathogenicity of T. gondii are related to proline metabolism. Methods The gene-edited strains of proline dehydrogenase (Tgprodh) were constructed by using clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR–Cas9) technology. The effects of the Tgprodh gene on the growth in vitro and pathogenicity in vivo of the tachyzoites for T. gondii were studied through proliferation, plaque, invasion, egress and virulence assays. The effects of the Tgprodh gene on mitochondrial function were studied by using reactive oxygen species (ROS), mitochondrial membrane potential (∆Ψm), adenosine triphosphate (ATP) assay kits, mitochondrial DNA (mtDNA) copy numbers, transmission electron microscopy (TEM) analysis, and reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). The effects of the Tgprodh gene on proline metabolism were studied by using l-proline (L-Pro), l-glutamic acid (L-Glu), l-glutamine (L-Gln) assay kits, and RT-qPCR. Results TgPRODH, the first rate-limiting enzyme in proline metabolism, was identified to be encoded by T. gondii and localized in the cytoplasm of T. gondii. Deletion of the Tgprodh gene resulted in significant growth inhibition in vitro and reduced pathogenicity in vivo of T. gondii. Further study found that deletion of the Tgprodh gene caused damage to the mitochondrial morphology, decreased membrane potential, mtDNA copy numbers, and the production of ATP and ROS. The expression of genes for maintaining mitochondrial integrity was downregulated in the Tgprodh-knockout strain of T. gondii, while complementation of the Tgprodh gene restored these defects in this parasite. Meantime, the deletion of the Tgprodh gene resulted in the accumulation of proline, reduced the contents of glutamate and glutamine, and affected the expression of genes related to proline catabolism in T. gondii. Conclusions The present study found the significance of the Tgprodh gene for the intracellular growth and pathogenicity of T. gondii through regulating mitochondrial function and the proline metabolism and provided a novel insight to reveal intracellular survival strategies of T. gondii. Graphical Abstract